2019
DOI: 10.1107/s2052252519003130
|View full text |Cite
|
Sign up to set email alerts
|

Structure and magnetic properties of W-type hexaferrites

Abstract: W-type hexaferrites (WHFs) (SrMe 2Fe16O27, Me = Mg, Co, Ni and Zn) are hard magnetic materials with high potential for permanent magnet applications owing to their large crystalline anisotropy and high cation tunability. However, little is known with regards to their complex structural and magnetic characteristics. Here, the substitution of metals (Me = Mg, Co, Ni and Zn) in WHFs is described and their crystal and magnetic structures investigated. From joined refinements of X-ray and neutron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…The obtained saturation magnetisation values correspond very well with the results reported in the literature, Mørch et al found SrZn 2 Fe 16 O 27 and SrNi 2 Fe 16 O 27 have saturation magnetisations of values 80.4(3) and 69.0(3) Am 2 kg −1 , respectively. 14 Likewise did J.-H. You et al find a M s of 77.3(2) Am 2 kg −1 for SrZn 2 Fe 16 O 27 in the study of the composition range SrZn x Fe 18− x O 27 , while the highest saturation was found for x = 1 with a value of 87.7(5) Am 2 kg −1 . 36 The samples reported by J.-H. You et al also have vanishing coercivity with values between 7.2–9.5 kA m −1 .…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…The obtained saturation magnetisation values correspond very well with the results reported in the literature, Mørch et al found SrZn 2 Fe 16 O 27 and SrNi 2 Fe 16 O 27 have saturation magnetisations of values 80.4(3) and 69.0(3) Am 2 kg −1 , respectively. 14 Likewise did J.-H. You et al find a M s of 77.3(2) Am 2 kg −1 for SrZn 2 Fe 16 O 27 in the study of the composition range SrZn x Fe 18− x O 27 , while the highest saturation was found for x = 1 with a value of 87.7(5) Am 2 kg −1 . 36 The samples reported by J.-H. You et al also have vanishing coercivity with values between 7.2–9.5 kA m −1 .…”
Section: Resultsmentioning
confidence: 67%
“…To obtain the intrinsic value of saturation magnetisation for the compounds Sr(Ni 1− x Zn x ) 2 Fe 16 O 27 ( x = 0, 0.5, 1) the corrected saturation magnetization is reported in Table 1 along with the wt% of the phases present. These corrections are described by Mørch et al 14 The weight fractions were extracted from the 2D Rietveld of the refinements of the synchrotron diffraction data, which will be described in detail below.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study we described the uniaxial magnetic ordering in SrZn 2 Fe 16 O 27 with the magnetic space group (MSG) P6 3 /mm 0 c 0 (further details given in Section S2.1), but did not determine the MSG of the planar ordering in SrCo 2 Fe 16 O 27 (Mørch et al, 2019). Fig.…”
Section: Magnetic Structurementioning
confidence: 99%
“…A system with potential conical spin ordering is the family of W-type hexaferrites, with Co 2+ substituting Fe 2+ as the transition metal. It is known that Co 2+ changes the magnetocrystalline anisotropy axis from uniaxial to planar at room temperature for SrCo 2Àx Zn x Fe 16 O 27 when x goes from 2 to 0 (Mørch et al, 2019). Here, three different magnetic structures of W-type hexaferrites are determined by neutron powder diffraction methods at room temperature.…”
Section: Introductionmentioning
confidence: 96%